FAS: Using FPGA to Accelerate and Secure SDN Software Switches. (17th January 2018) - Fu, Wenwen; Li, Tao; Sun, Zhigang
Abstract : Software-Defined Networking (SDN) promises the vision of more flexible and manageable networks but requires certain level of programmability in the data plane to accommodate different forwarding abstractions. SDN software switches running on commodity multicore platforms are programmable and are with low deployment cost. However, the performance of SDN software switches is not satisfactory due to the complex forwarding operations on packets. Moreover, this may hinder the performance of real-time security on software switch. In this paper, we analyze the forwarding procedure and identify the performance bottleneck of SDN software switches. An FPGA-based mechanism for accelerating and securing SDN switches, named FAS (FPGA-Accelerated SDN software switch), is proposed to take advantage of the reconfigurability and high-performance advantages of FPGA. FAS improves the performance as well as the capacity against malicious traffic attacks of SDN software switches by offloading some functional modules. We validate FAS on an FPGA-based network processing platform. Experiment results demonstrate that the forwarding rate of FAS can be 44% higher than the original SDN software switch. In addition, FAS provides new opportunity to enhance the security of SDN software switches by allowing the deployment of bump-in-the-wire security modules (such as packet detectors and filters) in FPGA.